2022
DOI: 10.13057/biodiv/d231226
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the medicinal plant in homegarden of local communities in the coastal area of Prigi Bay, Trenggalek, East Java, Indonesia

Abstract: Abstract. Agustina N, Hutauruk TJW, Sulistyaningrum N, Yudhanto SM, Liza N, Kusumaningrum L, Sugiyarto, Yasa A, Saensouk S, Naim DMD, Setyawan AD. 2022. Diversity of the medicinal plant in homegarden of local communities in the coastal area of Prigi Bay, Trenggalek, East Java, Indonesia. Biodiversitas 23: 6302-6312. Homegarden is a part of the agroforestry system that is essential in a food security program. It also reflects the social and traditional practices in certain areas that define the composition of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The study found that older adults (46 years and older) had the highest level of lexicon knowledge and use (81.4%) compared to other age groups. This finding is in line with the results of research (Agustina et al, 2022) which revealed that people aged 46-55 years have the highest knowledge about medicinal plants.…”
Section: Knowledge and Usage Levels Of Early Adult Speakerssupporting
confidence: 91%
See 1 more Smart Citation
“…The study found that older adults (46 years and older) had the highest level of lexicon knowledge and use (81.4%) compared to other age groups. This finding is in line with the results of research (Agustina et al, 2022) which revealed that people aged 46-55 years have the highest knowledge about medicinal plants.…”
Section: Knowledge and Usage Levels Of Early Adult Speakerssupporting
confidence: 91%
“…Furthermore, there is also research by (Kik et al, 2021) on the threat of language extinction in Papua which found a rapid decline in students' local language skills compared to their parents. The results of this research predict that there will Another relevant research that also measured community medicinal plant knowledge in the coastal area of Prigi Bay, Trenggalek, East Java was conducted by (Agustina et al, 2022). This study explored 32 families of 59 species of medicinal plants consumed for medicinal purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by [7] states that there are 40 types of medicinal plants used by the people of Asam Jawa village. Research by [8] There are 59 types of medicinal plants used by the community in Prigi Bay, Trenggalek, East Java. Among the types of medicinal plants, the most dominant medicinal plants which are used as the main ingredients of traditional medicine by the people of Namorambe Village, Deli Serdang Regency are from the Zingiberace Family namely as many as 8 species (Table 1), Solanaceae (4 species), Myrtacea (3 species), Euphorbiaceae (3 species).…”
Section: Resultsmentioning
confidence: 99%